Restoration of knee functions in football players after injuries - Makarova, E. V.; Egorov, D. E.; Kupreenko, M. V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to develop and test the effectiveness of individual physical rehabilitation programs for football players with knee injuries.